The use of Anti-Reflux therapy in patients with chronic rhinosinusitis associated with Laryngopharyngeal Reflux - Zabolotna, Diana; Ismahilov, Eldar; Kizim, Yaroslav (The Ukrainian Scientific Medical Youth Journal, 2026)
chronic rhinosinusitis is a persistent inflammatory condition of the nasal cavity and paranasal sinuses that lasts for at least three months and affects millions of individuals worldwide, representing a significant clinical and socioeconomic challenge due to its prolonged course, high symptom burden, and substantial recurrence rates even after optimized medical and surgical therapy. Although the disorder is widely recognized as multifactorial, with contributing elements such as impaired epithelial barrier function, altered microbiota composition, genetic susceptibility, environmental exposure, and dysregulated local and systemic immune responses, increasing attention has been directed toward the potential impact of laryngopharyngeal reflux as an overlooked but clinically important factor capable of sustaining inflammation in the upper aerodigestive tract. Experimental and clinical studies have demonstrated that refluxate containing pepsin and other gastric components may reach the nasopharynx and sinonasal mucosa, where it induces epithelial injury, promotes mucous hypersecretion, alters local microbial ecology, and triggers neurogenic inflammatory pathways, ultimately impairing mucociliary transport and facilitating bacterial colonization and secondary infection. Given that unsatisfactory postoperative outcomes remain a considerable problem and that reflux-related mucosal irritation has been implicated in delayed healing and disease persistence, the present study aimed to investigate whether postoperative antireflux treatment may influence symptom dynamics and recurrence rates in patients with chronic rhinosinusitis with or without nasal polyps who also exhibit signs of laryngopharyngeal reflux. A prospective clinical study included 52 patients examined at the Kolomiychenko Institute of Otolaryngology between 2023 and 2024. Patients were divided into two groups: 26 received proton pump inhibitor therapy with antacids in the postoperative period, while 26 did not. All underwent videoendoscopic rhinoscopy, laryngoscopy, and computed tomography of the paranasal sinuses. Symptoms were assessed by the Sino-Nasal Outcome Test-22, endoscopic manifestations by the Lund-Kennedy scoring system, and reflux status by the Reflux Symptom Index and Reflux Finding Score. Preoperatively, groups showed no significant differences. Three months after surgery, patients who received anti-reflux therapy had a significantly lower mean Sino-Nasal Outcome Test-22 score compared with controls, indicating greater symptom reduction, although endoscopic improvements were similar in both groups. During follow-up, recurrence was observed in 19.2% of treated patients and 30.8% of untreated patients, with a trend toward fewer recurrences under therapy, but without statistical significance due to limited sample size and short observation. The results confirm that signs of laryngopharyngeal reflux are common in patients with chronic rhinosinusitis and suggest that anti-reflux therapy may enhance symptom control and possibly reduce recurrence risk after surgery. Larger, long-term studies are needed to clarify the role of reflux management in comprehensive treatment strategies.